Motivational interviewing for the management of child and adolescent obesity: a systematic literature review - Romain Lutaud; Eva Mitilian; Jenny Forte; Gaetan Gentile; Rachel Reynaud; Camille Truffet; Thibault Bellanger (BJGP Open, 2023)
Background: Among children or adolescents with obesity, 40–70.5% will remain obese as adults according to their paediatric body mass index (BMI). The recommended management involves changes in their nutritional habits (diet, physical activity, and sedentary lifestyle). Motivational interviewing (MI), a patient-centred consultation, has proven its worth in many fields where acting on behaviours is essential. Aim: To investigate the use and outcomes of MI in the management of children and adolescents who are overweight and obese. Design & setting: A systematic review evaluated MI in the management of children and adolescents who are overweight and obese. Method: PubMed, Web of Science, Cochrane Library, and CISMeF were searched between January 2022 and March 2022 for following terms: ‘motivational interviewing’, ‘overweight or obesity’, ‘children or adolescent’ to identify randomised controlled trials (RCTs). Inclusion criteria were interventions involving MI in children or adolescents who were commonly (polygenically) overweight or obese. Exclusion criteria were: studies before 1991; and articles not written in English or French. The first stage of the selection process was carried out by reading the titles and abstracts. A second stage was carried out by reading the complete studies. A secondary inclusion of articles was carried out following the reading of bibliographic references, mainly from systematic reviews and meta-analyses. The data were summarised in synthetic tables based on the Population, Intervention, Comparison, Outcomes, and Study (PICOS) tool. Results: From 444 articles the review identified 26 RCTs. Statistically significant results were found for all criteria (anthropometric and behavourial) in both children and adolescents. Quality of life and depression scores were also improved. Parental presence in the interview appeared to be essential for children, whereas for adolescents, the supportive involvement of parents outside of the interviews seemed more appropriate. The frequency and duration of the interventions played a major role in obtaining results, as did the number of people involved, and the diversity of the places where they are taken care of. Conclusion: MI seems promising for children and adolescents with overweight or obesity, within the framework of a comprehensive, multiprofessional, family management, carried out over a long period with regular consultations.